Trends in Crop Production Changes in the Rural Areas of Al-Habbaniya ‎District - Rahma Mezhir Ibrahim; Ismael M. Khalifa (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: The study aimed to identify the problems that hinder agricultural production. The study also aimed to investigate the elements that would overcome the negative effects of the agricultural limitation investment in order to improve the level of plant agricultural production, which would enable the district and the governorate to achieve agricultural self-sufficiency. Methodology: The research relied on the regional approach to determine the current state of crop production in the rural areas of Al-Habbaniya district. The research also adopted the objective approach to examine the crops, the extent of changes in productivity, and the cultivated areas of crops in the district's rural areas. Results: After analyzing the data, the results showed that all natural and human factors contributed significantly to the reduction in the area of agricultural land and the actual cultivated areas. The area suitable for farming has decreased by (2876) dunams, and the actual cultivated area decreased by (31) dunams over two agricultural seasons (2009-2010) and (2021-2022). The results also showed that the wheat crop recorded a negative change of (-18) tons and a relative change of (1238.6). The relative index number showed a change of (98.6). The study also revealed that the total productivity of summer vegetables in Al-Habbaniya district recorded an absolute negative change of (-26.3) tons, a relative change of (274.6), and the relative index number reached (93.5